2006
DOI: 10.1158/0008-5472.can-06-2496
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Up-regulates the Expression of Vascular Endothelial Growth Factor, Matrix Metalloproteinase (MMP)-2, and MMP-9 in Nasopharyngeal Carcinoma Tumor Cells

Abstract: Recent studies using ovarian cancer cells have shown that the catecholamine hormones norepinephrine (norepi) and epinephrine (epi) may influence cancer progression by modulating the expression of matrix metalloproteinases (MMP) and vascular endothelial growth factor (VEGF). The purpose of this study is to determine if the stress hormone norepi can influence the expression of MMP-2, MMP-9, and VEGF in nasopharyngeal carcinoma (NPC) tumors by using three NPC tumor cell lines. The NPC cell lines HONE-1, HNE-1, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
268
2
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 356 publications
(300 citation statements)
references
References 41 publications
16
268
2
11
Order By: Relevance
“…1), rather than ionotropic receptors that directly gate ion channels in cellular membranes. 9 G proteins can affect various processes inside the cell, such as the level of cyclic AMP, and in doing so might influence carcinogenesis in complicated ways [60][61][62][63] that could have various time courses. A simple time course is that while a high level of NE is excessively stimulating its receptors on a cell, this increases the probability of immediately developing cancer within that cell; however, epidemiological drug studies suggest that there may be a significant delay, perhaps of many years.…”
Section: Literature Search Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…1), rather than ionotropic receptors that directly gate ion channels in cellular membranes. 9 G proteins can affect various processes inside the cell, such as the level of cyclic AMP, and in doing so might influence carcinogenesis in complicated ways [60][61][62][63] that could have various time courses. A simple time course is that while a high level of NE is excessively stimulating its receptors on a cell, this increases the probability of immediately developing cancer within that cell; however, epidemiological drug studies suggest that there may be a significant delay, perhaps of many years.…”
Section: Literature Search Detailsmentioning
confidence: 99%
“…These drugs may also help treat existing cancers since some cancerous cells have functional adrenoceptors. [60][61][62][63]74,80 As described earlier, reducing the activation of some adrenoceptor subtypes by lowering the level of NE or via a or b blocking drugs may actually increase carcinogenesis rather than decrease it, 79 and this may vary for different organs. And when examining whether NE drugs affect cancer rates, it is not only important to compare people who are taking these drugs for a condition such as hypertension with healthy control subjects (some of whom may be taking these drugs), but also with hypertensive people taking classes of drugs that do not affect the NE system.…”
Section: Literature Search Detailsmentioning
confidence: 99%
“…Many solid epithelial tumors express receptors for neuroendocrine mediators from the sympathetic nervous system (SNS) (the catecholamines, epinephrine and norepinephrine) (Mitra and Carraway 1999;Lutgendorf, Cole et al 2003;Nagmani, Pasco et al 2003;Palm, Lang et al 2006;Thaker, Han et al 2006;Ramos-Jimenez, Soria-Jasso et al 2007;Sastry, Karpova et al 2007) or the hypothalamus-pituitary-adrenal (HPA) axis (the glucocorticoid, cortisol) (Wu, Chaudhuri et al 2004). Analyses carried out in vitro and in mouse xenograft models have shown that neuroendocrine receptors regulate several biological processes involved in cancer metastasis and disease progression, including angiogenesis (Lutgendorf, Cole et al 2003;Thaker, Han et al 2006), tissue invasion (Sood, Bhatty et al 2006;Yang, Sood et al 2006), cell motility (Palm, Lang et al 2006), and programmed cell death (Wu, Chaudhuri et al 2004;Sastry, Karpova et al 2007). Analyses of mouse xenograft models also show that experimentally imposed behavioral stress can increase the growth and metastatic activity of implanted human carcinoma cells via direct neuroendocrine regulation of tumor cell biology (Thaker, Han et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, catecholamines can enhance the expression of several genes involved in angiogenesis (e.g., VEGF, IL6) and tissue invasion (MMP2, MMP9) in ovarian and asopharyngeal carcinoma cells (Lutgendorf, Cole et al 2003;Sood, Bhatty et al 2006;Yang, Sood et al 2006;Nilsson, Armaiz-Pena et al 2007). These effects are mediated by betaadrenergic receptors, and subsequent activation of the cyclic 3′,5′-adenosine monophosphate / protein kinase A (cAMP/ PKA) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Moreover, some stress neurotransmitters, such as norepinephrine (NE) and epinephrine (E), have been demonstrated to contribute to the regulation of tumour cell invasion, at least in part through b-AR activation. 6,7,9 Interactions between tumour cells and soluble factors originated from the nervous system has recently been proposed to favour metastasis formation. 10 Improved survival rates have been demonstrated in mice with metastatic tumour by combined administration of b-AR antagonists.…”
mentioning
confidence: 99%